The Effect of Single Identity Number Implementation, Tax Service Quality and Taxpayer Awareness on Taxpayer Compliance - Rahayu Lestari, Sri; Rissa Rizky Rahmawati, Maria; Aulia, Azra; Anand, Dev (Journal of Accounting and Finance Management, 2025)
Taxes serve as a means for enforcing or overseeing government policies related to social and economic issues. This inquiry focuses on how the method of implementing a unified identity number, the standard of tax services, and taxpayer consciousness affect the adherence levels of individual tax obligors. A quantitative approach is adopted, incorporating firsthand information collected via the distribution of questionnaires. The research focused on single tax filers who are enrolled at KPP Pratama Cirebon Dua. The sample consisted of 60 personal taxpayers, chosen using the saturated sampling method. Findings from this research reveal that the Single Identity Number (SIN) and taxpayer awareness positively and significantly influence tax adherence. Conversely, the standard of aid from tax authorities has an inconsequential and detrimental influence on compliance. Tax subject adherence is shaped by the Single Identity Number (SIN), the caliber of tax services, and the degree of tax remitter’s understanding.